Translation Shift of Adverbs of Manner In Reference to: “City of Bones: Mortal Instruments” by Cassandra Clare - Ilyanora Patricia, Jaynne; Putra Yadnya, Ida Bagus; Alit Ida Setianingsih, Ni Ketut (Udayana Journal of Social Sciences and Humanities; Vol 5 No 1 (2021): UJoSSH, February 2021DO - 10.24843/UJoSSH.2021.v05.i01.p07, 2021)
This study is entitled “Translation Shift of Adverbs of Manner in Reference to ‘City of Bones: Mortal Instruments’ by Cassandra Clare” . The aims are to identify the equivalences of adverbs of manner translated into Bahasa Indonesia and to analyze the shift of adverbs of manner in the novel. The data was collected by close-reading to identify the English adverbs of manner and its translation into Bahasa Indonesia found in the novel, highlighting the data found in both of the novels, comparing the data found to find the equivalences in both source and target language, then note-taking the data found to be analyzed afterward. The theories used in this research are the theory of translation proposed by Larson (1984) and the translation theory of shift proposed by Catford (2000). The results show that the English adverbs of manner found were equivalent to prepositions dengan, sambil, oleh, bagaikan, seperti, and secara that were followed with adjective, noun, verb, adjective phrase, noun phrase, verb phrase, or adverb after the preposition. The translation shift that occurred in the translation was category shift, in which the adverbs of manner shifted into an adjective, verbs, and numeral, and another type of translation shift that occurred was a level shift, in which adverbs of manner shifted adjective phrase, the noun phrase, and verb phrase.